(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Work activities that are not ergonomic when operating a computer for a long time and are carried out repeatedly will disrupt health, especially in disorders of work postures involving muscle function or commonly called Musculoskeletal Disorders (MSDs). The purpose of this study is to analyze the level of risk of MSDs in workers using computers so as to reduce the risk of MSDs. MSDs disorders that interfere with workers can be eliminated by distributing questionnaires. This study uses the Nordic Body Map (NBM) questionnaire which serves to identify complaints of muscle fatigue subjectively and uses the Rapid Office Strain Assessment (ROSA) method to analyze the high level of MSDs risk that is 69 with an individual average of 52.86. The results of the analysis using the ROSA method state that all employees do not have good office work facilities and are not in accordance with the principles of ergonomics. A final score of 6 signifies that work facilities owned by all work stations must be objectively employed. Research conducted at the Logistics Company involved 7 workers in different work departments to analyze work posture disorders. The results of the analysis using the NBM method in a study that has been carried out stated that the 15 locations of muscle at risk of injury and work station 1 had a improved score because the value was more than the safe limit of value 4. Improvements made to reduce the score were by redesigning the work station according to anthropometry of the human body. After designing the new work station and analyzing it with ROSA, the score finally changed to 3.